Fitoremediasi Logam Berat pada Limbah Cair Elektroplating Menggunakan Tanaman Rumput Gajah (Pennisetum purpureum) dan Alang-Alang (Imperata cylindrica) - Anidah H Triwulandari; Firra Rosariawari (Jurnal Serambi Engineering, 2025)
The electroplating industry produces liquid waste containing dissolved heavy metals, such as copper and nickel. If this waste is not managed properly, it has the potential to cause environmental pollution. One method that can be used to address this issue, particularly with regard to the heavy metal parameters Cu and Ni, is phytoremediation. Phytoremediation utilises plants to remove pollutants from the environment. Plants that can absorb heavy metals in this way include napier grass (Pennisetum purpureum) and speargrass (Imperata cylindrica). This study aims to determine the ability of these two plant species to absorb and remove heavy metals (Cu and Ni) from electroplating waste. The research was conducted using a batch system with variations in sampling time on days 7, 14, 21, 28 and 35. Napier grass produced the best results on day 21, with reduction efficiencies of 85.7% for Cu and 82.5% for Ni. Meanwhile, speargrass produced the most optimal results on day 35, reducing Cu by 89.2% and Ni by 87.3%. Based on these results, speargrass proved to be more effective than napier grass in reducing the levels of the heavy metals copper (Cu) and nickel (Ni) in electroplating waste.